2012
DOI: 10.1590/s0103-21002012000900007
|View full text |Cite
|
Sign up to set email alerts
|

Violence in daily hospital nursing work

Abstract: Objective: To describe the frequency of referred verbal, physical and sexual violence and factors associated with verbal violence in nursing teams' work at public hospitals. Methods: Cross-sectional study, involving 1509 workers at three public hospitals in Rio de Janeiro City -(RJ). Bivariate analysis and logistic regression were applied. Significance was set at 5%. Results: The frequencies of verbal, physical and sexual violence amounted to 982 (65.1%), 46 (3%) and 87 (5.7%), respectively. After applying mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 9 publications
7
19
0
2
Order By: Relevance
“…Victims of violence at work in the past year had lower average age than those not exposed to violence in the last year, reinforcing findings of other studies (5,9,12,18,(20)(21) . This result can be explained from the perspective of young professionals who have less expertise in the development of their work activities and thus would have less ability to prevent attacks.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Victims of violence at work in the past year had lower average age than those not exposed to violence in the last year, reinforcing findings of other studies (5,9,12,18,(20)(21) . This result can be explained from the perspective of young professionals who have less expertise in the development of their work activities and thus would have less ability to prevent attacks.…”
Section: Discussionsupporting
confidence: 83%
“…These data reveal the prevalence of victims in a recent period, featuring workplace violence as a phenomenon occurring in labor every day. Brazilian studies have identified a prevalence of 25-65% for some kind of violence in the last 12 months (9,18) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations